Insurance and medical resource allocation: a literature review - ying, liu (Advances in Social Sciences Research Journal, 2020)
The contribution of the existing research results of insurance and resource allocation in theory and policy proposition has important reference value for the study of the operation mechanism and policy orientation of insurance resource allocation. On the basis of combing the research path of the existing research results, this paper combines the insurance theory with the general economic theory, based on China's national conditions, tries to think and choose new research path with new thinking mode, and systematically and deeply discusses the effective allocation of China's insurance resources.